Estágio curricular supervisonado em filosofia e suas dobras: uma genealogia da formação filosófica na UFSM - Ribas, Jéssica Erd (2019)
The present Master's dissertation is part of the Post Graduation Program in Education (PPGE) of the Federal University of Santa Maria (UFSM). It belongs to Research Line 2 of this program, to be specific, Educational Public Policies, Educational Practices and their Interfaces. The research focuses on analyzing the discourse of Academic Projects and Reports produced by students who were attending Supervised Academic Internship in Philosophy I and II (ECS I and II) at UFSM during the years 2007 to 2016. The analysis considers Michel Foucault's theoretical and methodological perspective. We intended to understand and explore discourses, within the ambit of academic tradition, that led the trainees (prospective teachers at that time) to the process of subjectification and, consequently, to the practices of learning and teaching Philosophy. The paper seeks to answer the question: “What are the effects produced by discursive formations on Philosophy and teaching on the UFSM Philosophy trainee's subjectivation process?”. For the development of the research we used the genealogical studies of Foucault. According to his studies we pursued to understand and identify the relations of knowledge and power that are present in the discursive formations on Philosophy and philosophizing act. We examined the ECS interns’ Academic Projects and Reports for this purpose. Our results show that the teachers graduated in Philosophy from UFSM experience philosophy based on the exegesis of classical texts and on the history of Western philosophical thought through practices inherited from the Uspian French structural method. We hypothesize that this cultural background does not contribute to the formation of teachers who can philosophize, in other words, teachers who have experience in philosophizing and creating concepts about things. However, we show that the heritage is not hegemonic as there are possibilities for renewal of this academic tradition.